Delineation of the minimal hepatitis B surface antigen-specific B- and T-cell epitope contained within an anti-idiotype-derived pentadecapeptide. - Rajadhyaksha, M (1995)
A pentadecapeptide (2F10 peptide) is capable of mimicking the group-specific "a" determinant of human hepatitis B surface antigen (HBsAg) at both the B- and the T-cell level. This peptide represents a sequence on the heavy-chain hypervariable region of a monoclonal "internal image" anti-idiotype (anti-id 2F10) that has partial sequence homology to the "a" determinant epitope of HBsAg. To identify the exact location of the B- and T-cell epitopes, four truncated peptides (peptides 1-4) were synthesized. Using these truncated peptides we have identified the minimal sequence (octapeptide 3) that represents a functional B- and T-cell epitope capable of generating HBsAg-specific antibodies and T cells. This to our knowledge represents the first example of a short peptide sequence functioning as both a B- and a T-cell epitope. We have also identified another T-cell epitope (2F10 peptide 4), but this peptide fails to elicit HBsAg-specific B cells and T cells. Thus, the 2F10 pentadecapeptide is composed of two nonoverlapping, functional T-cell epitopes only one of which is HBsAg specific. Since peptide 3 represents the complementarity-determining region and peptide 4 represents the framework region of the anti-id 2F10, we conclude that an 8-aa sequence from the complementarity-determining region of anti-id 2F10 is sufficient for the molecular mimicry of HBsAg. Finally, our experiments suggest that sequences flanking the minimal immunodominant epitope exert a considerable influence on the nature of antigenic processing that occurs and the resultant T-cell reactivity elicited.